HYGIENE DAN SANITASI KANTIN SELINGKUNGAN UNIVERSITAS NEGERI PADANG - ALEN, ANGGI TANIA; Yusuf, Liswati; Yulastri, Asmar (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research was motivated by a problem in the cafeteria in the State University of Padang who have not noticed aspects of hygiene and sanitation. The purpose of this study was to determine how the application of hygiene and environmental sanitation in the cafeteria seen Padang State University of indicator buildings, sanitary facilities, and personal hygiene. This research is descriptive quantitative. The sampling technique was purposive sampling conducted as many as 38 employees from 8 cafeteria. The instrument used in this study a questionnaire (questionnaire) Likert scale. Data analysis technique is the technique used to determine the level of attainment percentage of respondents from each of the indicators studied. Based on the results obtained from the data that the hygiene and sanitation of existing canteen building in the State University of Padang is in the category of less well with the percentage achieved by 56 %, the indicator sanitation facilities are in the unfavorable category with a score of 55 %, and also be an indicator of personal hygiene the unfavorable category with the percentage achieved by 68 % of respondents. Keywords : hygiene, sanitation, canteens, personal hygiene